Liquid crystal alignment agent, liquid crystal alignment film and liquid crystal element
Patent Information
- Application Number
- JP2021088359
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-29
- Filing Date
- 2021-05-26
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-05-26
AI Technical Summary
【0010】 本発明の液晶配向剤によれば、残像が生じにくく、塗布性に優れ、かつ力学強度が高い液晶配向膜を得ることができる。特に本発明の液晶配向剤によれば、AC残像特性及びDC残像特性を両立できる液晶配向膜を得ることができる。
Smart Images

Figure 0007639548000001 
Figure 0007639548000002 
Figure 0007639548000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal alignment film, and a liquid crystal device. [Background technology]
[0002] As the liquid crystal material for liquid crystal elements, negative type liquid crystal is used in liquid crystal elements of the VA driving system, MVA driving system, etc., while positive type liquid crystal is used in liquid crystal elements of the TN type, IPS (In-Plane Switching) driving system, FFS (Fringe Field Switching) driving system, etc. In recent years, it has also been proposed to use negative type liquid crystal in liquid crystal elements of the IPS driving system or FFS driving system in order to achieve even higher resolution of liquid crystal elements (for example, see Patent Document 1).
[0003] In recent years, liquid crystal elements have been applied to a wide range of applications, from relatively large display devices such as liquid crystal televisions and information displays to small display devices such as smartphones. As liquid crystal elements are used in a wider variety of applications, there is a demand for even higher quality liquid crystal elements. In light of this, it has been proposed to incorporate a polymer having a nitrogen-containing metharylene structure into a liquid crystal alignment agent, thereby obtaining a liquid crystal alignment film with low resistance and high transparency, and to obtain a liquid crystal element with little burn-in (DC afterimage) caused by accumulated charges (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 152928 [Patent Document 2] International Publication No. 2019 / 093037 Summary of the Invention [Problem to be solved by the invention]
[0005] In addition to DC afterimages, there are also AC afterimages that occur in liquid crystal elements due to the alignment direction of liquid crystals shifting from the initial alignment. In order to suppress the occurrence of afterimages and achieve even higher definition in liquid crystal elements, it is required to be able to suppress not only DC afterimages but also AC afterimages. In addition, when a metharylene structure is introduced into a polymer as in the technology of Patent Document 2, there is a concern that the solubility of the polymer will decrease due to the introduction of a rigid structure into the main chain, and the applicability of the liquid crystal alignment agent will decrease. Furthermore, when a liquid crystal alignment film is obtained by a rubbing method, or when considering the suppression of a decrease in yield, a film formed using a liquid crystal alignment agent is required to have high mechanical strength. However, it is difficult to simultaneously satisfy these multiple characteristics, and there is room for further improvement in the liquid crystal alignment agent.
[0006] The present invention has been made in consideration of the above problems, and has as its main object to provide a liquid crystal aligning agent which is less likely to cause afterimages, has good coatability, and is capable of producing a liquid crystal alignment film with high mechanical strength. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by using a plurality of polymers having different molecular structures, thereby completing the present invention. Specifically, the present invention provides the following means.
[0008] <1> A liquid crystal aligning agent comprising: a polymer [A] having the following structural unit (U1) but not the following structural unit (U2); and a polymer [B] having the following structural unit (U2) and the following structural unit (U3). Structural unit (U1): A structural unit derived from a diamine having a partial structure represented by the following formula (1): Structural unit (U2): A structural unit derived from a diamine having a partial structure represented by the following formula (2): Structural unit (U3): A structural unit derived from a diamine having the following partial structure Y Substructure Y:-(CH2) n - (wherein n is an integer of 1 to 20), -(CH2)n+1 In the structure represented by the formula -, any methylene group is -O-, -S-, -COO-, -NR 7 -, -NR 7 -CO-, -NR 7 -COO-, -NR 7 -CO-NR 8 -, or a structure in which the ring is replaced by a nitrogen-containing non-aromatic heterocyclic group (provided that R 7 and R 8 are each independently a hydrogen atom or a monovalent organic group. When n is 2 or more, -O-, -S-, -COO-, -NR 7 -, -NR 7 -CO-, -NR 7 -COO-, -NR 7 -CO-NR 8 - and nitrogen-containing non-aromatic heterocyclic groups are not adjacent to each other. 7 -CO-, -NR 7 -COO- or -NR 7 -CO-NR 8 - [ka] (In formula (1), X 1 and X 2 are each independently a divalent aromatic ring group. 1 The aromatic ring of 1 There are no substituents bonded to the positions other than the bond position of "X" and the bond position of the group bonded to "*", 2 The aromatic ring of 2 The substituent is not bonded to the position other than the bonding position of R and the bonding position of the group bonded to "*". 1 and R 2 Y each independently represents a single bond, an alkanediyl group having 1 to 10 carbon atoms, or a substituted alkanediyl group having 1 to 10 carbon atoms. 1 and Y 2 are each independently * 1 -NR 3 -CO- or * 1 -CO-NR 3 -It is. 3 is a hydrogen atom or a monovalent organic group.1 " is Z 1 It represents a bond with Z. 1 is a single bond or a divalent organic group. m is 0 or 1. When m is 0, R 1 and R 2 At least one of the groups is an alkanediyl group or a substituted alkanediyl group having 1 to 10 carbon atoms. "*" represents a bond.) [ka] (In formula (2), A 1 and A 2 are each independently a divalent aromatic ring group. 1 -NR 4 - or a divalent aromatic heterocyclic group. 1 When R is a divalent aromatic heterocyclic group, 5 and R 6 are each independently a hydrogen atom or a monovalent organic group. 1 Ga-NR 4 -If R 4 , R 5 and R 6 is either (i) or (ii) below. (i)R 4 R is a hydrogen atom or a monovalent organic group. 5 and R 6 are each independently a hydrogen atom or a monovalent organic group, or R 5 and R 6 and are combined together to form A 1 , -NR 4 - and A 2 It represents a ring structure formed together with (ii)R 4 and R 5 are each independently a hydrogen atom or a monovalent organic group, or R 4 and R 5 and are combined together to form A 1 and a nitrogen atom. 6 is a hydrogen atom or a monovalent organic group. "*" indicates a bond.)
[0009] <2> the above <1> A liquid crystal alignment film formed by the liquid crystal alignment agent. <3> the above <2> A liquid crystal element comprising the liquid crystal alignment film. Effect of the Invention
[0010] According to the liquid crystal aligning agent of the present invention, it is possible to obtain a liquid crystal alignment film that is less likely to cause image retention, has excellent coating properties, and has high mechanical strength. In particular, according to the liquid crystal aligning agent of the present invention, it is possible to obtain a liquid crystal alignment film that can achieve both AC image retention and DC image retention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The liquid crystal aligning agent of the present disclosure contains a polymer [A] and a polymer [B] which is a polymer different from the polymer [A]. Each component contained in the liquid crystal aligning agent of the present disclosure and other components that are optionally blended as necessary will be described below.
[0012] In this specification, the term "hydrocarbon group" includes chain-shaped hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-shaped hydrocarbon group" refers to a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure in the main chain and are composed only of a chain structure. However, they may be saturated or unsaturated. The term "alicyclic hydrocarbon group" refers to a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, it is not necessary to be composed only of an alicyclic hydrocarbon structure, and it also includes those that have a chain structure as a part. The term "aromatic hydrocarbon group" refers to a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, it is not necessary to be composed only of an aromatic ring structure, and it may include a chain structure or an alicyclic hydrocarbon structure as a part. The term "structural unit" refers to a unit that mainly constitutes the main chain structure and is contained in at least two or more units in the main chain structure. Unless otherwise specified, each component and each compound may be used alone or in combination of two or more types.
[0013] <Polymer [A]> The polymer [A] is a polymer having a structural unit (U1) derived from a diamine having a partial structure represented by the following formula (1) (hereinafter also referred to as "specific diamine (A)"). [ka] (In formula (1), X 1 and X 2 are each independently a divalent aromatic ring group. 1 The aromatic ring of 1 There are no substituents bonded to the positions other than the bond position of "X" and the bond position of the group bonded to "*", 2 The aromatic ring of 2 The substituent is not bonded to the position other than the bonding position of R and the bonding position of the group bonded to "*". 1 and R 2 Y each independently represents a single bond, an alkanediyl group having 1 to 10 carbon atoms, or a substituted alkanediyl group having 1 to 10 carbon atoms. 1 and Y 2 are each independently 1 -NR 3 -CO- or * 1 -CO-NR 3 -It is. 3 is a hydrogen atom or a monovalent organic group. 1 " is Z 1 It represents a bond with Z. 1 is a single bond or a divalent organic group. m is 0 or 1. R 1 and R 2 At least one of the groups is an alkanediyl group or a substituted alkanediyl group having 1 to 10 carbon atoms. "*" represents a bond.)
[0014] Structural unit (U1) The structural unit (U1) has two aromatic rings and at least one amide bond (-NR 3 In the above formula (1), X is a structural unit derived from a diamine containing —CO—. 1 and X 2 The divalent aromatic ring group of X is preferably an aromatic hydrocarbon group. 1 , X 2Specific examples of the group include groups obtained by removing any two hydrogen atoms bonded to carbon atoms constituting an aromatic hydrocarbon ring such as a benzene ring, a naphthalene ring, or an anthracene ring.
[0015] In addition, X 1 and X 2 The aromatic ring of X has no substituent. 1 The aromatic ring of 1 No substituents are bonded to the bond position of X and the bond position of the group bonded to the bond represented by "*". 2 The aromatic ring of 2 and the bonding position of the group bonded to the bond represented by "*".
[0016] In order to increase the density of the liquid crystal alignment film, and to reduce the residual image and increase the mechanical strength of the film, 1 and X 2 The divalent aromatic ring group is preferably a phenylene group, and particularly preferably a 1,4-phenylene group.
[0017] R 1 and R 2 is an alkanediyl group having 1 to 10 carbon atoms, R 1 and R 2 Examples of R include linear alkanediyl groups such as a methylene group, an ethylene group, a 1,3-propanediyl group, a 1,4-butanediyl group, and a 1,5-pentanediyl group; and branched alkanediyl groups such as a 1,2-propanediyl group, a 1,2-butanediyl group, and a 2-methyl-1,3-propanediyl group. 1 and R 2 When is a substituted alkanediyl group having 1 to 10 carbon atoms, examples of the substituent include a halogen atom, a hydroxyl group, an amino group, a cyano group, an alkoxy group, a protected hydroxyl group, and a protected amino group.
[0018] R 1 and R 2At least one of R is preferably an alkanediyl group having 1 to 10 carbon atoms or a substituted alkanediyl group having 1 to 10 carbon atoms. 1 and R 2 Both R are preferably alkanediyl groups having 1 to 10 carbon atoms or substituted alkanediyl groups having 1 to 10 carbon atoms. 1 and R 2 The carbon number of R is preferably 1 to 8, and more preferably 2 to 8, in terms of exhibiting good voltage retention characteristics and liquid crystal alignment properties. 1 and R 2 is preferably linear.
[0019] Y 1 and Y 2 is an amide bond (* 1 -NR 3 -CO- or * 1 -CO-NR 3 -). R 3 The monovalent organic group of R is preferably a monovalent hydrocarbon group having 1 to 10 carbon atoms or a group (protecting group) that generates a hydrogen atom upon elimination. 3 When is a monovalent hydrocarbon group, the monovalent hydrocarbon group is preferably an alkyl group having 1 to 3 carbon atoms or a phenyl group, more preferably an alkyl group having 1 to 3 carbon atoms.
[0020] R 3 is a protecting group, the protecting group is preferably a monovalent group that is detached by heat, and examples thereof include carbamate-based protecting groups, amide-based protecting groups, imide-based protecting groups, and sulfonamide-based protecting groups. Of these, carbamate-based protecting groups are preferred in terms of their high detachability by heat, and specific examples thereof include tert-butoxycarbonyl group, benzyloxycarbonyl group, 1,1-dimethyl-2-haloethyloxycarbonyl group, allyloxycarbonyl group, 2-(trimethylsilyl)ethoxycarbonyl group, 9-fluorenylmethyloxycarbonyl group, and allyloxycarbonyl group. Of these, tert-butoxycarbonyl group (Boc group) is particularly preferred in terms of its excellent detachability by heat and its ability to reduce the amount of the deprotected portion remaining in the film.
[0021] R 3 is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a protecting group, and particularly preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a tert-butoxycarbonyl group.
[0022] Z 1 is a single bond or a divalent organic group. Z is preferred because it can improve the voltage retention characteristics and liquid crystal alignment properties of a liquid crystal element. 1 is preferably a divalent organic group.
[0023] Z 1 is a divalent organic group, the divalent organic group is a divalent hydrocarbon group having 1 to 20 carbon atoms, -O-, -S- or -NR 3 -(However, R 3 is Y 1 and Y 2 R in 3 (Same meaning as Z) 1 is Y 1 and Y 2 It is bonded to the amide bond via a hydrocarbon group.
[0024] Z is preferred because it can increase the solubility of the polymer [A]. 1 Among these, the divalent organic group is a divalent chain hydrocarbon group having 1 to 20 carbon atoms, a divalent alicyclic hydrocarbon group having 4 to 20 carbon atoms, or a chain hydrocarbon group having -O-, -S- or -NR between the carbon-carbon bonds. 3 A divalent group having - is preferable, and an alkanediyl group having 1 to 20 carbon atoms or a cycloalkylene group having 4 to 12 carbon atoms is particularly preferable. Z 1 The number of carbon atoms is preferably 1 to 12, and more preferably 1 to 10. m is 0 or 1, and is preferably 1 in that it can enhance the effect of reducing AC afterimages.
[0025] The specific diamine (A) is preferably an aromatic diamine, and in particular, is preferably an aromatic diamine having a structure that allows the partial structure represented by the above formula (1) to be introduced into the main chain of the polymer [A]. Specifically, the specific diamine (A) is particularly preferably a compound represented by the following formula (DA). The term "main chain" refers to the "trunk" portion of the polymer, which is the longest chain of atoms. It is permissible for this "trunk" portion to contain a ring structure. For example, "having a specific structure in the main chain" refers to the specific structure constituting a part of the main chain. The term "side chain" refers to a portion branched from the "trunk" of the polymer. [ka] (In formula (DA), R 1 , R 2 , Y 1 , Y 2 , Z 1 and m are defined as in formula (1) above.
[0026] In the above formula (DA), R 1 , R 2 , Y 1 , Y 2 , Z 1 For illustrative and preferred examples of and m, the explanation of formula (1) above applies.
[0027] Specific examples of the specific diamine (A) include compounds represented by the following formulas (DA-1) to (DA-23). [ka] [ka] [ka] (In the formula, "Boc" represents a tert-butoxycarbonyl group.)
[0028] The polymer [A] may be any polymer having the structural unit (U1), but is preferably at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide, in terms of being able to form a liquid crystal alignment film having high affinity with liquid crystals and high mechanical strength, and being highly reliable. When the polymer [A] is at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide, the partial structure represented by the above formula (1) can be introduced into the main chain of the polymer [A]. In addition, by introducing the partial structure represented by the above formula (1) into the main chain of the polymer, the effect of reducing the afterimage and improving the film strength can be further enhanced, which is preferable.
[0029] (Polyamic acid) When the polymer [A] is a polyamic acid, the polyamic acid (hereinafter also referred to as “polyamic acid [A]”) can be obtained, for example, by reacting a tetracarboxylic dianhydride with a diamine compound containing a specific diamine (A).
[0030] Tetracarboxylic acid dianhydride Examples of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [A] include aliphatic tetracarboxylic dianhydrides, alicyclic tetracarboxylic dianhydrides, and aromatic tetracarboxylic dianhydrides. Specific examples of these include aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butanetetracarboxylic dianhydride and ethylenediaminetetraacetic dianhydride; alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, and the like. -dione, 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride, cyclopentanetetracarboxylic dianhydride, cyclohexanetetracarboxylic dianhydride, etc.; as aromatic tetracarboxylic dianhydrides, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, ethylene glycol bisanhydrotrimate, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-carbonyldiphthalic anhydride, etc.; and tetracarboxylic dianhydrides described in JP-A-2010-97188 can be used. As the tetracarboxylic dianhydride, one type can be used alone or two or more types can be used in combination.
[0031] The tetracarboxylic dianhydride used in the synthesis of the polyamic acid [A] preferably contains at least one compound selected from the group consisting of aliphatic tetracarboxylic dianhydrides and alicyclic tetracarboxylic dianhydrides, and more preferably contains alicyclic tetracarboxylic dianhydrides, in that it is possible to obtain a liquid crystal alignment film that has high solubility in a solvent and exhibits good electrical properties and low afterimage properties. The proportion of the alicyclic tetracarboxylic dianhydride used is preferably 20 mol % or more, more preferably 40 mol % or more, and even more preferably 50 mol % or more, based on the total amount of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [A].
[0032] Diamine compounds The diamine compound used in the synthesis of the polyamic acid [A] may be the specific diamine (A) alone, but may also be used together with the specific diamine (A) and a diamine different from the specific diamine (A) (hereinafter also referred to as "other diamine (A)"). Examples of the other diamine (A) include aliphatic diamines, alicyclic diamines, aromatic diamines, and diaminoorganosiloxanes. Specific examples of the other diamines (A) include p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylpropane, 4-aminophenyl-4-aminobenzoate, 2,5-diaminobenzoic acid, 3,5-diaminobenzoic acid, 1,5-bis(4-aminophenoxy)pentane, 1,2-bis(4-aminophenoxy)ethane, 1,3-bis(4-aminophenoxy)propane, 1,6-bis(4-aminophenoxy)hexane, 4,4'-diaminodiphenyl ether, N,N'-di(5-amino-2-pyridyl)-N,N'-di(tert-butoxycarbonyl)ethylenediamine, 6,6'-(pentamethylenedioxy)bis(3-aminopyridine), and 2,2'-dimethyl-4,4'-diaminobiphenyl.
[0033] In the synthesis of polyamic acid [A], the ratio of the specific diamine (A) is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, even more preferably 30 mol% or more, even more preferably 40 mol% or more, and particularly preferably 60 mol% or more, based on the total amount of diamine compounds used in the synthesis of polyamic acid [A], from the viewpoint of sufficiently reducing residual images and obtaining a liquid crystal alignment film with high mechanical strength. The ratio of the specific diamine (A) can be set within a range of 100 mol% or less based on the total amount of diamine compounds used in the synthesis of polyamic acid [A].
[0034] Synthesis of polyamic acid The polyamic acid [A] can be obtained by reacting a tetracarboxylic dianhydride with a diamine compound, optionally together with a molecular weight modifier. In the synthesis reaction of the polyamic acid, the ratio of the tetracarboxylic dianhydride to the diamine compound is preferably such that the acid anhydride group of the tetracarboxylic dianhydride is 0.2 to 2 equivalents per equivalent of the amino group of the diamine compound. Examples of the molecular weight modifier include acid monoanhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride, monoamine compounds such as aniline, cyclohexylamine, and n-butylamine, and monoisocyanate compounds such as phenyl isocyanate and naphthyl isocyanate. The ratio of the molecular weight modifier to be used is preferably 20 parts by mass or less per 100 parts by mass of the total of the tetracarboxylic dianhydride and diamine compound used.
[0035] The synthesis reaction of polyamic acid is preferably carried out in an organic solvent. The reaction temperature is preferably -20°C to 150°C, and the reaction time is preferably 0.1 to 24 hours. Examples of organic solvents used in the reaction include aprotic polar solvents, phenolic solvents, alcoholic solvents, ketone solvents, ester solvents, ether solvents, halogenated hydrocarbons, and hydrocarbons. Specific examples of these include one or more selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, tetramethylurea, hexamethylphosphortriamide, m-cresol, xylenol, and halogenated phenols, or a mixture of one or more of these with other organic solvents (e.g., butyl cellosolve, diethylene glycol diethyl ether, etc.). The amount of the organic solvent (a) used is preferably an amount such that the total amount (b) of the tetracarboxylic dianhydride and the diamine is 0.1 to 50% by mass based on the total amount (a+b) of the reaction solution.
[0036] In this manner, a polymer solution in which the polyamic acid [A] is dissolved is obtained. This polymer solution may be used as it is for the preparation of a liquid crystal alignment agent, or the polyamic acid [A] contained in the polymer solution may be isolated and then used for the preparation of a liquid crystal alignment agent.
[0037] (Polyamic acid ester) When the polymer [A] is a polyamic acid ester, the polyamic acid ester can be obtained, for example, by a method of reacting a polyamic acid [A] with an esterifying agent, a method of reacting a tetracarboxylic acid diester with a diamine compound containing a specific diamine (A), or a method of reacting a tetracarboxylic acid diester dihalide with a diamine compound containing a specific diamine (A). The polyamic acid ester may have only an amic acid ester structure, or may be a partially esterified product in which an amic acid structure and an amic acid ester structure coexist. The reaction solution in which the polyamic acid ester is dissolved may be used as it is for the preparation of a liquid crystal alignment agent, or the polyamic acid ester contained in the reaction solution may be isolated and then used for the preparation of a liquid crystal alignment agent.
[0038] (Polyimide) When the polymer [A] is a polyimide, the polyimide can be obtained, for example, by dehydrating and cyclizing the polyamic acid [A] synthesized as described above to convert it into an imidized product. The polyimide may be a complete imidized product in which all amic acid structures of the polyamic acid precursor are dehydrated and cyclized, or a partial imidized product in which only a part of the amic acid structures are dehydrated and cyclized, and an amic acid structure and an imide ring structure coexist. The imidization rate of the polyimide is preferably 20 to 99%, more preferably 30 to 90%. The imidization rate is the ratio of the number of imide ring structures to the total number of amic acid structures and the number of imide ring structures of the polyimide, expressed as a percentage. Here, a part of the imide rings may be isoimide rings.
[0039] The dehydration ring-closing of polyamic acid is preferably carried out by dissolving polyamic acid in an organic solvent, adding a dehydrating agent and a dehydration ring-closing catalyst to the solution, and heating as necessary. In this method, the dehydrating agent may be, for example, an acid anhydride such as acetic anhydride, propionic anhydride, or trifluoroacetic anhydride. The amount of the dehydrating agent used is preferably 0.01 to 20 moles per mole of the amic acid structure of the polyamic acid. The dehydration ring-closing catalyst may be, for example, a tertiary amine such as pyridine, collidine, lutidine, or triethylamine. The amount of the dehydration ring-closing catalyst used is preferably 0.01 to 10 moles per mole of the dehydrating agent used. The organic solvent used in the dehydration ring-closing reaction may be the organic solvent exemplified as the one used in the synthesis of polyamic acid. The reaction temperature in the dehydration ring-closing reaction is preferably 0 to 180° C. The reaction time is preferably 1.0 to 120 hours. The reaction solution containing the polyimide may be used for the preparation of a liquid crystal aligning agent as it is, or the polyimide may be isolated and then used for the preparation of a liquid crystal aligning agent.
[0040] <Polymer [B]> The polymer [B] is a polymer having a structural unit (U2) and a structural unit (U3). Each structural unit contained in the polymer [B] will be described in detail below.
[0041] Structural unit (U2) The structural unit (U2) is a structural unit derived from a diamine having a partial structure represented by the following formula (2) (hereinafter also referred to as "specific diamine (B1)"). The structural unit (U2) imparts to the polymer [B] the function of reducing accumulated charges in the liquid crystal alignment film. The above-mentioned polymer [A] does not have the structural unit (U2), and in this respect, the polymer [B] is different from the polymer [A]. [ka] (In formula (2), A 1 and A 2 are each independently a divalent aromatic ring group. 1 -NR 4- or a divalent aromatic heterocyclic group. 1 When R is a divalent aromatic heterocyclic group, 5 and R 6 are each independently a hydrogen atom or a monovalent organic group. 1 Ga-NR 4 -If R 4 , R 5 and R 6 is either (i) or (ii) below. (i)R 4 R is a hydrogen atom or a monovalent organic group. 5 and R 6 are each independently a hydrogen atom or a monovalent organic group, or R 5 and R 6 and are combined together to form A 1 , -NR 4 - and A 2 It represents a ring structure formed together with (ii)R 4 and R 5 are each independently a hydrogen atom or a monovalent organic group, or R 4 and R 5 and are combined together to form A 1 and a nitrogen atom. 6 is a hydrogen atom or a monovalent organic group. "*" indicates a bond.)
[0042] In this specification, the fact that at least one of the multiple polymers contained in the liquid crystal alignment agent has a structural unit (hereinafter referred to as a "specific unit") in another polymer means that the other polymer is allowed to have the specific unit within a range that does not impair the effects of the present invention. When the other polymer does not have a specific unit, the content of the specific unit in the other polymer is preferably 1 mol % or less, more preferably 0.5 mol % or less, and even more preferably 0.1 mol or less, based on the total structural units in the other polymer.
[0043] In the above formula (2), A 1 and A 2Examples of the divalent aromatic ring group include a divalent aromatic hydrocarbon group and a divalent aromatic heterocyclic group. Examples of the divalent aromatic heterocyclic group include a nitrogen-containing aromatic heterocyclic group, an oxygen-containing aromatic heterocyclic group, and a sulfur-containing aromatic heterocyclic group, and the nitrogen-containing aromatic heterocyclic group is preferred. 1 and A 2 may have a substituent in the aromatic ring portion. Examples of the substituent include an alkyl group having 1 to 5 carbon atoms and a halogen atom.
[0044] A 1 , A 2 Specific examples of the divalent aromatic hydrocarbon group include a group obtained by removing any two hydrogen atoms bonded to carbon atoms constituting a benzene ring, a naphthalene ring, or an anthracene ring; a divalent nitrogen-containing aromatic heterocyclic group includes a group obtained by removing any two hydrogen atoms bonded to carbon atoms constituting a pyridine ring, a pyrimidine ring, a pyridazine ring, or a pyrazine ring; a divalent oxygen-containing aromatic heterocyclic group includes a group obtained by removing any two hydrogen atoms bonded to carbon atoms constituting a furan ring; and a divalent sulfur-containing aromatic heterocyclic group includes a group obtained by removing any two hydrogen atoms bonded to carbon atoms constituting a thiophene ring. From the viewpoint of achieving high density and high transmittance of the liquid crystal alignment film, A 1 and A 2 The divalent aromatic ring group is preferably a divalent aromatic hydrocarbon group, more preferably a phenylene group.
[0045] B 1 -NR 4 - or a divalent aromatic heterocyclic group. 1 When A is a divalent aromatic heterocyclic group, the aromatic heterocyclic group is 1 , A 2 Among these, B 1 The divalent aromatic heterocyclic group is preferably a group obtained by removing any two hydrogen atoms bonded to carbon atoms constituting a pyrrole ring, a furan ring, or a thiophene ring, in view of its high effect of alleviating accumulated charges.
[0046] B 1 When R is a divalent aromatic heterocyclic group, 5 and R 6 R is each independently a hydrogen atom or a monovalent organic group. 5 Specific and preferred examples of R 3 The explanation of R can be used. 6 Examples of the monovalent organic group include an alkyl group having 1 to 3 carbon atoms, a halogen atom, and a cyano group.
[0047] B 1 Ga-NR 4 -If R 4 , R 5 and R 6 satisfies (i) or (ii) above. 4 , R 5 and R 6 If satisfies (i) above, then R 4 R is a hydrogen atom or a monovalent organic group. 4 Specific and preferred examples of R 3 The explanation of R can be used. 5 and R 6 Specific and preferred examples of when R is a hydrogen atom or a monovalent organic group are similar to those described above. 3 The explanation of R can be used. 5 and R 6 But R 5 and R 6 and are combined together to form A 1 , -NR 4 - and A 2 When a ring structure is formed together with the above, examples of the ring structure include a carbazole structure, a 9-methylcarbazole structure, and a 9-ethylcarbazole structure.
[0048] R 4 , R 5 and R 6 If satisfies (ii) above, then R 4 Specific and preferred examples of when is a hydrogen atom or a monovalent organic group are described above for R 3 The explanation of R can be used. 5 and R6 When is a hydrogen atom or a monovalent organic group, examples of the monovalent organic group include an alkyl group having 1 to 3 carbon atoms, a halogen atom, and a cyano group. R 4 and R 5 But R 4 and R 5 and are combined together to form A 1 and when it forms a ring structure together with the nitrogen atom, examples of the ring structure include an indoline structure and an isoindoline structure.
[0049] Preferable specific examples of the partial structure represented by the above formula (2) include B 1 Ga-NR 4 In the case where - is -, the partial structures represented by each of the following formulas (2-1) to (2-7) are 1 When is a divalent aromatic heterocyclic group, partial structures represented by each of the following formulas (2-8) to (2-10) can be mentioned. [ka] (In formulas (2-1) to (2-10), R 4 and R 33 are each independently a hydrogen atom or a monovalent organic group. "*" represents a bond.)
[0050] The specific diamine (B1) may have only one partial structure represented by the above formula (2), or may have two or more partial structures. From the viewpoint of ensuring the solubility of the polymer [B], the number of partial structures is preferably one or two. The specific diamine (B1) is preferably an aromatic diamine, and in particular, is preferably an aromatic diamine having a structure capable of introducing the partial structure represented by the above formula (2) into the main chain of the polymer [B]. Specific examples of the specific diamine (B1) include compounds represented by each of the following formulas (DB-1) to (DB-21). The specific diamine (B1) does not have the partial structure Y of the structural unit (U3). [ka] [ka] [ka]
[0051] Structural unit (U3) The structural unit (U3) is a structural unit derived from a diamine having the following partial structure Y (hereinafter also referred to as "specific diamine (B2)"). The specific diamine (B2) is a compound that does not have the partial structure represented by the above formula (2) and is different from the specific diamine (B1). The polymer [B2] has the structural unit (U3) together with the structural unit (U2), so that the solubility of the polymer [B2] can be increased and a liquid crystal alignment film exhibiting low image retention characteristics (particularly, reduced AC image retention) can be obtained. Substructure Y:-(CH2) n - (wherein n is an integer of 1 to 20), -(CH2) n+1 In the structure represented by the formula -, any methylene group is -O-, -S-, -COO-, -NR 7 -, -NR 7 -CO-, -NR 7 -COO-, -NR 7 -CO-NR 8 -, or a structure in which the ring is replaced by a nitrogen-containing non-aromatic heterocyclic group (provided that R 7 and R 8 are each independently a hydrogen atom or a monovalent organic group. When n is 2 or more, -O-, -S-, -COO-, -NR 7 -, -NR 7 -CO-, -NR 7 -COO-, -NR 7 -CO-NR 8 - and nitrogen-containing aromatic heterocyclic groups are not adjacent to each other. 7 -CO-, -NR 7 -COO- or -NR 7 -CO-NR 8 -
[0052] In the partial structure Y, n is preferably 1 to 14, more preferably 1 to 12, from the viewpoint of improving the solubility of the polymer [B], improving the low image retention characteristics (reduction of AC image retention and DC image retention), and the mechanical strength of the liquid crystal alignment film. n+1 In the structure represented by -, when any methylene group is replaced with -O- or the like (hereinafter also referred to as a "heteroatom-containing structure"), n is preferably 2 or more, and more preferably 2 to 14. In the partial structure Y, examples of the nitrogen-containing non-aromatic heterocyclic group include a piperidine-1,4-diyl group, a piperazine-1,4-diyl group, and a 2-oxo-4-imidazolidinone-1,3-diyl group. R 7 and R 8 For illustrative and preferred examples, see above R 3 The explanation given in the above can be used. As the partial structure Y, -(CH2) n -, a heteroatom-containing structure, or -O- is preferred, and -(CH2) n - or a heteroatom-containing structure is more preferred.
[0053] The specific diamine (B2) is not particularly limited as long as it is a diamine having a partial structure Y, and examples thereof include aliphatic diamines, alicyclic diamines, aromatic diamines, diaminoorganosiloxanes, etc. The specific diamine (B2) preferably has a structure that allows the partial structure Y to be introduced into the main chain of the polymer [B], and specifically, is preferably a compound represented by the following formula (DB2). [ka] (In formula (DB2), Y 3 is -(CH2) n -, -(CH2) n+1 In the structure represented by the formula -, any methylene group is -O-, -S-, -COO-, -NR 7 -, -NR 7 -CO-, -NR 7 -COO-, -NR 7-CO-NR 8 -, or a structure in which it is replaced by a nitrogen-containing non-aromatic heterocyclic group (heteroatom-containing structure), -O-, -S-, -COO-, -NR 7 -CO-, -NR 7 -COO- or -NR 7 -CO-NR 8 -It is. 3 and A 4 are each independently a single bond, a substituted or unsubstituted cyclohexylene group, or a substituted or unsubstituted phenylene group. 7 and R 8 When n is 2 or more, in the heteroatom-containing structure, -O-, -S-, -COO-, -NR 7 -, -NR 7 -CO-, -NR 7 -COO-, -NR 7 -CO-NR 8 - and the nitrogen-containing non-aromatic heterocyclic groups are not adjacent to one another.
[0054] Specific examples of the specific diamine (B2) include aliphatic diamines such as metaxylylenediamine, pentamethylenediamine, and hexamethylenediamine; alicyclic diamines such as 4,4'-methylenebis(cyclohexylamine); and aromatic diamines such as 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylpropane, 4-aminophenyl-4-aminobenzoate, 4,4'-diaminobenzanilide, 1,3-bis(4-aminophenyl)urea, 1,3-bis(4-aminophenethyl)urea, 1,3-bis(4-aminobenzyl)urea, 1,5-bis(4-aminophenoxy)pentane, 1,2-bis(4-aminophenoxy)ethane, 1,3-bis(4-aminophenoxy)propane, 1,6-bis(4-amino Examples of the diaminoorganosiloxane include 1,3-bis(3-aminopropyl)-2,3-dimethylphenyl ether, 1,4 ... [ka]
[0055] As the specific diamine (B2), it is preferable to use at least one selected from the group consisting of 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenyl ether, 1,2-bis(4-aminophenoxy)ethane, 4,4'-[4,4'-propane-1,3-diylbis(piperidine-1,4-diyl)]dianiline, bis[2-(4-aminophenyl)ethyl]hexanedioic acid, diethylene glycol bis(4-aminophenyl)ether, hexamethylenediamine, and the compound represented by the above formula (DC-5).
[0056] The polymer [B] is preferably at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide, in view of its high affinity with the polymer [A]. In particular, the polymer [B] is suitable in that it has the partial structure represented by the above formula (2) and the partial structure Y in its main chain, thereby enhancing the solubility of the polymer [B], quickly alleviating the accumulated charge, and sufficiently reducing AC image retention.
[0057] When the polymer [B] is a polyamic acid, the polyamic acid (hereinafter also referred to as "polyamic acid [B]") can be obtained by reacting a tetracarboxylic dianhydride with a diamine compound containing a specific diamine (B1) and a specific diamine (B2). The polyamic acid [B], polyamic acid ester, and polyimide that are the polymer [B] can be produced in the same manner as the polymer [A].
[0058] As the tetracarboxylic dianhydride used in the synthesis of the polymer [B], the explanation of the examples and preferred examples of the tetracarboxylic dianhydride used in the synthesis of the polymer [A] can be used. That is, the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [B] preferably contains at least one compound selected from the group consisting of an aliphatic tetracarboxylic dianhydride and an alicyclic tetracarboxylic dianhydride, and more preferably contains an alicyclic tetracarboxylic dianhydride. The proportion of the alicyclic tetracarboxylic dianhydride used is preferably 20 mol% or more, more preferably 40 mol% or more, and even more preferably 50 mol% or more, based on the total amount of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [B].
[0059] In addition, when synthesizing the polyamic acid [B], polyamic acid ester, and polyimide, which are the polymer [B], a compound different from the specific diamine (B1) and the specific diamine (B2) (hereinafter also referred to as "other diamine (B)") may be further used as a diamine compound. Examples of the other diamine (B) include p-phenylenediamine, 3,5-diaminobenzoic acid, 2,5-diaminobenzoic acid, 4,4-diamino-2,2'-dimethylbiphenyl, and 3,5-diamino-N,N-bis(pyridin-3-ylmethyl)benzamide. In the synthesis, the amount of the other diamine (B) used is preferably 20 mol% or less, more preferably 10 mol% or less, based on the total amount of the diamine compound used in the synthesis of the polymer [B].
[0060] In the synthesis of the polymer [B], the amount of the specific diamine (B1) used is preferably 5 mol% or more, more preferably 10 mol% or more, and even more preferably 15 mol% or more, based on the total amount of the diamine compounds used in the synthesis of the polymer [B], in order to quickly relieve residual charges and sufficiently reduce DC afterimages. In addition, in order to suppress AC afterimages and ensure the solubility of the polymer [B], the amount of the specific diamine (B1) used is preferably 95 mol% or less, more preferably 80 mol% or less, and even more preferably 70 mol% or less, based on the total amount of the diamine compounds used in the synthesis of the polymer [B].
[0061] The amount of the specific diamine (B2) used is preferably 5 mol % or more, more preferably 10 mol % or more, and even more preferably 15 mol % or more, based on the total amount of the diamine compounds used in the synthesis of the polymer [B], in order to increase the solubility of the polymer [B]. In addition, from the viewpoint of sufficiently reducing DC afterimages, the amount of the specific diamine (B2) used is preferably 90 mol % or less, more preferably 80 mol % or less, and even more preferably 70 mol % or less, based on the total amount of the diamine compounds used in the synthesis of the polymer [B].
[0062] Regarding the various conditions in the synthesis method of each polymer such as the polyamic acid [B], the above explanation of the polymer [A] can be applied.
[0063] The solution viscosity of the polymer [A] and the polymer [B] used in the preparation of the liquid crystal alignment agent is preferably 10 to 800 mPa·s when the polymer is made into a 10% by mass solution, and more preferably 15 to 500 mPa·s. The solution viscosity (mPa·s) is a value measured at 25°C using an E-type rotational viscometer for a 10% by mass polymer solution prepared using a good solvent for the polymer (e.g., γ-butyrolactone, N-methyl-2-pyrrolidone, etc.).
[0064] The weight average molecular weight (Mw) of each of the polymers [A] and [B] measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn) represented by the ratio of Mw to the number average molecular weight (Mn) measured by GPC in terms of polystyrene is preferably 7 or less, more preferably 5 or less.
[0065] In the liquid crystal alignment agent, the content of the polymer [A] is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the total amount of the polymer components contained in the liquid crystal alignment agent, from the viewpoint of sufficiently reducing AC afterimages. Also, the content of the polymer [A] is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on the total amount of the polymer components contained in the liquid crystal alignment agent, from the viewpoint of reducing DC afterimages by relaxing residual charges.
[0066] The content of the polymer [B] is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the total amount of the polymer components contained in the liquid crystal alignment agent. The content of the polymer [B] is preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 95% by mass or less, and even more preferably 90% by mass or less, based on the total amount of the polymer components contained in the liquid crystal alignment agent.
[0067] <Other ingredients> The liquid crystal alignment agent may contain, in addition to the polymer [A] and the polymer [B], components different from the polymer [A] and the polymer [B] (hereinafter also referred to as "other components"), if necessary.
[0068] (Other polymers) The liquid crystal alignment agent of the present disclosure may contain a polymer (hereinafter also referred to as "other polymer") different from the polymer [A] and the polymer [B] as a polymer component. The main skeleton of the other polymer is not particularly limited. Examples of the other polymer include polyamic acid, polyamic acid ester, polyimide, polyorganosiloxane, polyester, polyenamine, polyurea, polyamide, polyamideimide, polybenzoxazole precursor, polybenzoxazole, cellulose derivative, polyacetal, (meth)acrylic polymer, styrene polymer, maleimide polymer, or styrene-maleimide polymer. From the viewpoint of high affinity with liquid crystal when used in combination with the polymer [A] and the polymer [B] and high reliability of the liquid crystal element, the other polymer is preferably at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.
[0069] When other polymers are contained in the liquid crystal alignment agent, the content of the other polymers in the liquid crystal alignment agent is preferably 30 mass % or less, more preferably 20 mass % or less, even more preferably 10 mass % or less, and even more preferably 5 mass % or less, based on the total amount of the polymer [A], the polymer [B], and the other polymers.
[0070] (solvent) The liquid crystal aligning agent of the present disclosure is prepared as a liquid composition in which the polymer [A], the polymer [B], and other components used as necessary are preferably dispersed or dissolved in a suitable solvent.
[0071] As the solvent, an organic solvent is preferably used.Specific examples thereof include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,2-dimethyl-2-imidazolidinone, 1,3-dimethyl-2-imidazolidinone, phenol, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, diacetone alcohol, 1-hexanol, 2-hexanol, propane-1,2-diol, 3-methoxy-1-butanol, ethylene glycol monomethyl ether, methyl lactate, ethyl lactate, butyl lactate, methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, ethyl acetoacetate, ethyl propionate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, and ethylene glycol-i-propyl ether. ether, ethylene glycol-n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisopentyl ether, ethylene carbonate, propylene carbonate, propylene glycol monomethyl ether (PGME), diethylene glycol diethyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol diacetate, cyclopentanone, cyclohexanone, and the like.
[0072] Other components contained in the liquid crystal alignment agent include, in addition to the above, for example, antioxidants, metal chelate compounds, curing accelerators, surfactants, fillers, dispersants, photosensitizers, etc. The blending ratio of other components can be appropriately selected according to each compound within a range that does not impair the effects of the present disclosure.
[0073] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of the components other than the solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably in the range of 1 to 10 mass %. When the solid content concentration is 1 mass % or more, the thickness of the coating film can be sufficiently ensured, and a liquid crystal alignment film exhibiting good liquid crystal alignment properties is easily obtained. On the other hand, when the solid content concentration is 10 mass % or less, the coating film can be made to have an appropriate thickness, and a liquid crystal alignment film exhibiting good liquid crystal alignment properties is easily obtained, and the viscosity of the liquid crystal alignment agent becomes appropriate, tending to improve the coatability.
[0074] <Liquid crystal alignment film and liquid crystal element> The liquid crystal alignment film of the present disclosure is manufactured by the liquid crystal alignment agent prepared as described above. The liquid crystal element of the present disclosure includes a liquid crystal alignment film formed by using the liquid crystal alignment agent described above. The driving method of the liquid crystal in the liquid crystal element is not particularly limited, and can be applied to various modes such as TN type, STN type, VA type (including VA-MVA type, VA-PVA type, etc.), IPS type, FFS type, OCB (Optically Compensated Bend) type, PSA (Polymer Sustained Alignment) type, etc. The liquid crystal element can be manufactured by a method including, for example, the following steps 1 to 3. In step 1, the substrate used differs depending on the desired operation mode. Steps 2 and 3 are common to each operation mode.
[0075] <Step 1: Formation of coating film> First, a liquid crystal alignment agent is applied onto a substrate, and a coating film is formed on the substrate, preferably by heating the applied surface. As the substrate, for example, a transparent substrate made of glass such as float glass or soda glass; or plastic such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, or poly(alicyclic olefin) can be used. As the transparent conductive film provided on one side of the substrate, a NESA film (registered trademark of US PPG) made of tin oxide (SnO2), an ITO film made of indium oxide-tin oxide (In2O3-SnO2), etc. can be mentioned. When manufacturing a TN type, STN type, or VA type liquid crystal element, two substrates on which a patterned transparent conductive film is provided are used. On the other hand, when manufacturing an IPS type or FFS type liquid crystal element, a substrate on which an electrode patterned into a comb tooth shape is provided and an opposing substrate on which no electrode is provided are used.
[0076] The method of applying the liquid crystal alignment agent to the substrate is not particularly limited, and can be, for example, a spin coat method, a printing method (e.g., offset printing method, flexographic printing method, etc.), an inkjet method, a slit coat method, a bar coater method, an extrusion die method, a direct gravure coater method, a chamber doctor coater method, an offset gravure coater method, an impregnation coater method, an MB coater method, etc.
[0077] After the liquid crystal alignment agent is applied, preheating (prebaking) is preferably performed for the purpose of preventing dripping of the applied liquid crystal alignment agent. The prebaking temperature is preferably 30 to 200° C., and the prebaking time is preferably 0.25 to 10 minutes. Thereafter, the solvent is completely removed, and a baking (postbaking) step is performed, if necessary, for the purpose of thermally imidizing the amic acid structure present in the polymer. The baking temperature (postbaking temperature) at this time is preferably 80 to 280° C., more preferably 80 to 250° C. The postbaking time is preferably 5 to 200 minutes. The thickness of the film formed is preferably 0.001 to 1 μm.
[0078] <Step 2: Alignment Treatment> When manufacturing a TN-type, STN-type, IPS-type or FFS-type liquid crystal element, the coating film formed in the above step 1 is subjected to a treatment (alignment treatment) for imparting liquid crystal alignment ability. This imparts the alignment ability of liquid crystal molecules to the coating film, forming a liquid crystal alignment film. As the alignment treatment, it is preferable to use a rubbing treatment in which the surface of the coating film formed on the substrate is rubbed with cotton or the like, or a photo-alignment treatment in which the coating film is irradiated with light to impart liquid crystal alignment ability. When manufacturing a vertical alignment type liquid crystal element, the coating film formed in the above step 1 may be used as it is as a liquid crystal alignment film, or the coating film may be subjected to an alignment treatment in order to further enhance the liquid crystal alignment ability.
[0079] The light irradiation for photo-alignment can be performed by a method of irradiating the coating film after the post-bake step, a method of irradiating the coating film after the pre-bake step but before the post-bake step, or a method of irradiating the coating film during heating in at least one of the pre-bake step and the post-bake step. For example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used as the radiation to be irradiated to the coating film. Preferably, ultraviolet light containing light with a wavelength of 200 to 400 nm is used. When the radiation is polarized, it may be linearly polarized or partially polarized. When the radiation used is linearly polarized or partially polarized, the radiation may be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When the radiation is non-polarized, the radiation is irradiated in an oblique direction.
[0080] Examples of the light source used include a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. The radiation dose is preferably 200 to 30,000 J / m 2 and more preferably 500 to 10,000 J / m 2After the light irradiation for imparting the alignment ability, the surface of the substrate may be washed with, for example, water, an organic solvent (e.g., methanol, isopropyl alcohol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, etc.) or a mixture thereof, or the substrate may be heated.
[0081] <Step 3: Construction of liquid crystal cell> Two substrates on which the liquid crystal alignment film is formed are prepared as described above, and a liquid crystal is placed between the two substrates arranged opposite to each other to manufacture a liquid crystal cell. For example, the liquid crystal cell can be manufactured by placing two substrates opposite to each other with a gap between them so that the liquid crystal alignment film faces each other, bonding the peripheries of the two substrates with a sealant, injecting liquid crystal into the cell gap surrounded by the substrate surfaces and the sealant, and sealing the injection hole, or by a method using the ODF method. As the sealant, for example, an epoxy resin containing a hardener and aluminum oxide spheres as a spacer can be used. As the liquid crystal, either a positive type or a negative type may be used, but a negative type is preferred. As the negative type liquid crystal, for example, "MLC-6608", "MLC-6609", "MLC-6610", "MLC-7026-100" manufactured by Merck Co., Ltd. can be used. In particular, when a negative type liquid crystal is used in an IPS type or FFS type liquid crystal element, it is preferable in that the transmission loss at the upper part of the electrode can be reduced and the contrast can be improved. The liquid crystal may be a nematic liquid crystal or a smectic liquid crystal, with the nematic liquid crystal being preferred.
[0082] When manufacturing a liquid crystal display device, a polarizing plate is subsequently attached to the outer surface of the liquid crystal cell to obtain a liquid crystal display element. Examples of the polarizing plate include a polarizing film called an "H film" made by absorbing iodine while stretching and aligning polyvinyl alcohol, sandwiched between cellulose acetate protective films, and a polarizing plate made of the H film itself.
[0083] The liquid crystal element of the present invention can be effectively applied to various applications, specifically, for example, it can be used as various display devices such as clocks, portable game machines, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays, as well as light control devices, retardation films, and the like. EXAMPLES
[0084] Hereinafter, the embodiments will be described in more detail with reference to examples, but the present invention should not be construed as being limited to the following examples.
[0085] In the following examples, the imidization rate of polyimide in the polymer solution was measured by the following method. The required amounts of the raw material compounds and polymers used in the following examples were ensured by repeating the synthesis on a synthesis scale shown in the following synthesis examples as necessary. [Imidization rate of polyimide] The polyimide solution was poured into pure water, and the resulting precipitate was thoroughly dried under reduced pressure at room temperature. It was then dissolved in deuterated dimethyl sulfoxide and measured at room temperature using tetramethylsilane as a standard substance. 1 H-NMR was measured. 1 The imidization rate [%] was calculated from the H-NMR spectrum using the following formula (1). Imidization rate [%] = (1-(β1 / (β2×α))) × 100 … (1) (In formula (1), β1 is the peak area derived from the proton of the NH group appearing at a chemical shift of about 10 ppm, β2 is the peak area derived from other protons, and α is the ratio of the number of other protons to one proton of the NH group in the polymer precursor (polyamic acid).)
[0086] The abbreviations for the monomers used in the examples are as follows. (Tetracarboxylic acid dianhydride) Compound (c-1) to compound (c-5): Compounds represented by the following formulas (c-1) to (c-5), respectively. [ka]
[0087] (Diamine compounds) Compound (DA-1) to Compound (DA-14): Compounds represented by the above formulas (DA-1) to (DA-14), respectively Compound (DB-1) to Compound (DB-20): Compounds represented by the above formulas (DB-1) to (DB-20), respectively Compound (d-1) to compound (d-5): Compounds represented by the following formulas (d-1) to (d-5), respectively Compound (b-1) to compound (b-11): Compounds represented by the following formulas (b-1) to (b-11), respectively [ka] [ka]
[0088] <Polymer synthesis> 1. Synthesis of polyamic acid [Synthesis Example 1] 100 parts by mole of compound (c-2) as a tetracarboxylic dianhydride and 100 parts by mole of compound (DA-1) as a diamine compound were dissolved in N-methyl-2-pyrrolidone (NMP) and reacted at room temperature for 6 hours to obtain a solution containing 15% by mass of polyamic acid (referred to as "polymer (PAA-1)"). [Synthesis Examples 2-17, 23-46] Solutions containing polyamic acids (polymers (PAA-2) to (PAA-41)) were obtained by the same procedure as in Synthesis Example 1, except that the types and amounts of the tetracarboxylic dianhydrides and diamine compounds used were changed as shown in Tables 1 and 2 below. In Tables 1 and 2, the amount of tetracarboxylic dianhydride blended represents the ratio (mol %) to the total amount of tetracarboxylic dianhydride used in the synthesis of each polymer. The amount of diamine compound blended represents the ratio (mol %) to the total amount of diamine compound used in the synthesis of each polymer.
[0089] 2. Synthesis of Polyimide [Synthesis Example 18] 90 mol parts of compound (c-1) and 10 mol parts of compound (c-5) as tetracarboxylic dianhydride, and 100 mol parts of compound (DA-2) as diamine compound were dissolved in NMP, and the reaction was carried out at room temperature for 6 hours to obtain a solution containing 15% by mass of polyamic acid. Next, NMP was added to the obtained polyamic acid solution to obtain a solution with a polyamic acid concentration of 10% by mass, and pyridine and acetic anhydride were added to perform a dehydration ring-closing reaction at 60° C. for 4 hours. After the dehydration ring-closing reaction, the solvent in the system was replaced with fresh NMP to obtain a solution containing 15% by mass of polyimide with an imidization rate of about 80% (this is referred to as "polymer (PI-1)"). [Synthesis Examples 19-22] Solutions containing polyimides (polymers (PI-2) to (PI-5)) were obtained in the same manner as in Synthesis Example 18, except that the types and amounts of the tetracarboxylic dianhydrides and diamine compounds used were changed as shown in Table 1 below.
[0090] [Table 1]
[0091] [Table 2]
[0092] [Example 1] 1. Preparation of Liquid Crystal Alignment Agent The solution of the polymer (PAA-1) obtained in Synthesis Example 1 and the solution of the polymer (PAA-36) obtained in Synthesis Example 41 were diluted with NMP and butyl cellosolve (BC) to obtain a solution with a solid concentration of 4.0 mass% and a solvent composition ratio of NMP:BC = 80:20 (mass ratio). The solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (R-1).
[0093] 2. Fabrication of FFS-type liquid crystal cells using the rubbing method A glass substrate (first substrate) having a flat electrode (bottom electrode), an insulating layer, and a comb-shaped electrode (top electrode) laminated in this order on one side thereof, and a glass substrate (second substrate) having no electrode were prepared. Next, a liquid crystal alignment agent (R-1) was applied to each of the electrode-forming surface of the first substrate and one side of the second substrate using a spinner, and heated (pre-baked) on a hot plate at 110°C for 3 minutes. Then, the ...0 minutes in an oven at 230°C with the inside of the oven replaced with nitrogen, and a coating film having an average thickness of 0.08 μm was formed. Next, a rubbing treatment was performed on the coating film surface using a rubbing machine having a roll wrapped with rayon cloth at a roll rotation speed of 1000 rpm, a stage moving speed of 3 cm / sec, and a pile pressing length of 0.3 mm. Then, ultrasonic cleaning was performed in ultrapure water for 1 minute, and then drying was performed in a clean oven at 100°C for 10 minutes to obtain a pair of substrates having a liquid crystal alignment film. Next, a pair of substrates having a liquid crystal alignment film was screen-printed with an epoxy resin adhesive containing aluminum oxide spheres having a diameter of 3.5 μm, leaving a liquid crystal injection port at the edge of the surface on which the liquid crystal alignment film was formed. The substrates were then superimposed and pressed together, and the adhesive was thermally cured at 150°C for 1 hour. Next, a negative liquid crystal (MLC-6608, manufactured by Merck) was filled into the gap between the pair of substrates through the liquid crystal injection port, and the liquid crystal injection port was then sealed with an epoxy adhesive. Furthermore, in order to remove flow alignment during liquid crystal injection, the substrate was heated at 120°C and then slowly cooled to room temperature to produce a liquid crystal cell. When the pair of substrates were superimposed, the rubbing method of each substrate was set to be antiparallel.
[0094] 3. Evaluation of inkjet coating properties (evaluation of solubility) As the substrate to which the liquid crystal alignment agent was applied, a glass substrate with a transparent electrode made of ITO was used, which had been heated on a hot plate at 200°C for 1 minute, and then subjected to ultraviolet / ozone cleaning to reduce the water contact angle of the transparent electrode surface to 10° or less. The liquid crystal alignment agent (R-1) prepared in 1 above was applied onto the transparent electrode surface of the glass substrate with the transparent electrode using an inkjet coater (manufactured by Shibaura Mechatronics Co., Ltd.). The application conditions were 2,500 times / (nozzle·min), discharge amount of 250 mg / 10 seconds, and two round trips (total of four times). After application, the substrate was left to stand for 1 minute and then heated at 80°C to form a coating film with an average thickness of 0.1 μm. The obtained coating film was observed with the naked eye for unevenness and the number of repellings under irradiation with an interference fringe measurement lamp (sodium lamp). When the total number of unevenness and cissing spots was 0, it was rated as "excellent (◎)", when the total number of unevenness and cissing spots was 1 to less than 3, it was rated as "good (◯)", and when the total number of unevenness and cissing spots was 3 or more, it was rated as "poor (×)". When the inkjet coatability is good, it can be said that the polymer used in the preparation of the liquid crystal alignment agent has good solubility. As a result, the inkjet coatability of the liquid crystal alignment agent of this example was "excellent".
[0095] 4. Evaluation of AC image retention characteristics For the FFS type liquid crystal cell manufactured in 2. above, after driving it for 72 hours at an AC voltage of 10 V, the minimum relative transmittance (%) expressed by the following formula (2) was measured using an apparatus in which a polarizer and an analyzer were placed between a light source and a light detector. Minimum relative transmittance (%) = (β-B0) / (B100-B0) × 100 … (2) (In formula (2), B0 is the amount of light transmitted in a blank under crossed Nicols. B100 is the amount of light transmitted in a blank under paranicols. β is the minimum amount of light transmitted when a liquid crystal cell is sandwiched between a polarizer and an analyzer under crossed Nicols.) The black level in the dark state is expressed by the minimum relative transmittance of the liquid crystal cell, and in the case of an FFS type liquid crystal cell, the smaller the black level in the dark state, the better the contrast characteristics and AC afterimage characteristics. A minimum relative transmittance of less than 0.3% was rated "excellent (◎)", 0.3% or more but less than 2.0% was rated "good (◯)", and 2.0% or more was rated "poor (×)". As a result, this example was rated "excellent".
[0096] 5.Evaluation of Electrical Characteristics The FFS type liquid crystal cell manufactured in 2 above was placed in an oven at 60°C, and then the voltage holding ratio (VHR) was measured under the conditions of 1V and 1670msec using a VHR measuring device "VHR-1" manufactured by Toyo Technica Corporation. The evaluation criteria were "excellent (◎)" when the VHR was 80% or more, "good (○)" when it was less than 80% and 70% or more, "fair (△)" when it was less than 70% and 60% or more, and "unfair (×)" when it was less than 60%. As a result, the VHR of this example was evaluated as "excellent".
[0097] 6. Evaluation of reliability after light exposure The reliability of the FFS type liquid crystal cell manufactured in 2 above was evaluated. The evaluation was performed as follows. First, a voltage of 1V was applied to the liquid crystal cell for 60 microseconds, and then the voltage holding ratio (VHR1) was measured 1670 milliseconds after the voltage was removed. Next, the liquid crystal cell was irradiated with CCFL (backlight) at 60°C for one week, and then left to cool naturally to room temperature by standing at room temperature. After cooling, a voltage of 1V was applied to the liquid crystal cell for 60 microseconds, and then the voltage holding ratio (VHR2) was measured 1670 milliseconds after the voltage was removed. The measurement device used was a VHR measurement device "VHR-1" manufactured by Toyo Corporation. The rate of change in VHR (ΔVHR) at this time was calculated from the difference between VHR1 and VHR2 (ΔVHR=VHR1-VHR2), and the reliability was evaluated based on ΔVHR. When ΔVHR was less than 10%, it was judged as "excellent (◎)", when it was 10% or more and less than 15%, it was judged as "good (○)", when it was 15% or more and less than 20%, it was judged as "fair (△)", and when it was 20% or more, it was judged as "not good (×)". As a result, the reliability of this example was "excellent".
[0098] 7. Evaluation of DC image retention characteristics The liquid crystal cell manufactured in 2. above was driven at AC2.5V to set the luminance difference between any two pixels to 0, and then DC1V was applied to only one of the pixels for 20 minutes while driving at AC2.5V to accumulate charge. When the application of DC1V was stopped and the drive was returned to AC2.5V only, a luminance difference occurred between the two pixels due to the accumulated charge. By observing the change over time in this luminance difference, the relaxation time during the process of the residual DC value attenuation was calculated. A relaxation time of less than 10 seconds was judged as "excellent (◎)", a relaxation time of 10 to 20 seconds was judged as "good (◯)", and a relaxation time of 20 seconds or more was judged as "poor (×)". As a result, this example was rated as "excellent".
[0099] 8. Evaluation of rubbing resistance The liquid crystal alignment agent (R-1) prepared in 1 above was applied onto a glass substrate using a spinner, and heated (pre-baked) on a hot plate at 110°C for 3 minutes. After that, the substrate was dried (post-baked) for 30 minutes in an oven at 230°C with nitrogen substitution in the chamber, forming a coating film with an average thickness of 0.08 μm, and the haze value of the coating film was measured using a hazemeter. Next, the coating film was subjected to rubbing treatment five times using a rubbing machine having a roll wrapped with cotton cloth at a roll rotation speed of 1000 rpm, a stage moving speed of 3 cm / sec, and a pile indentation length of 0.3 mm. After that, the haze value of the liquid crystal alignment film was measured using a haze meter, and the difference from the haze value before the rubbing treatment (haze change value) was calculated using the following formula (3). Haze change value (%) = [haze value (%) of film after rubbing treatment] - [haze value (%) of film before rubbing treatment] ... (3) The rubbing resistance of the liquid crystal alignment film was evaluated as "excellent (◎)" when the haze change value was less than 0.8, "good (○)" when the haze change value was 0.8 or more and less than 1.5, and "poor (×)" when the haze change value was 1.5 or more. If the haze change value is less than 1.5 (more preferably less than 0.8), it can be said that the film strength is sufficiently high and the rubbing resistance is excellent. As a result, the rubbing resistance of this example was "excellent".
[0100] [Examples 2 to 21 and Comparative Examples 1 to 8] A liquid crystal alignment agent was prepared in the same manner as in Example 1, except that the composition of the liquid crystal alignment agent was changed as shown in Table 3 below. In addition, an FFS-type liquid crystal cell was produced by a rubbing method in the same manner as in Example 1 using the obtained liquid crystal alignment agent, and various evaluations were performed. The results are shown in Table 4 below. In Table 3, the blending amount indicates the blending amount (parts by mass) of each polymer in solid content with respect to the total amount of the polymer components used in the preparation of the liquid crystal alignment agent.
[0101] [Examples 22 and 23] A liquid crystal alignment agent was prepared in the same manner as in Example 1, except that the composition of the liquid crystal alignment agent was changed as shown in Table 3 below, and the liquid crystal alignment film was formed by a photo-alignment method instead of a rubbing method, and an FFS-type liquid crystal cell was manufactured and various evaluations were performed. The results are shown in Table 4. The liquid crystal alignment film was formed by the photo-alignment method as follows. (Formation of liquid crystal alignment film by photoalignment method) A liquid crystal alignment agent was applied using a spinner onto each of a glass substrate having a flat electrode (bottom electrode), an insulating layer, and a comb-shaped electrode (top electrode) laminated in this order on one side, and an opposing glass substrate on which no electrode was provided, and then heated (pre-baked) on a hot plate at 80°C for 1 minute. The substrate was then dried (post-baked) for 30 minutes in an oven at 230°C with the interior replaced with nitrogen, forming a coating film with an average thickness of 0.1 μm. The resulting coating film was irradiated with 1,000 J / m2 of linearly polarized ultraviolet light containing a 254 nm emission line using an Hg-Xe lamp. 2 The coating film was irradiated with light from the normal direction of the substrate to perform a photo-alignment treatment. The amount of irradiation was measured using an actinometer that measures at a wavelength of 254 nm. Next, the coating film that had been subjected to the photo-alignment treatment was heated in a clean oven at 230°C for 30 minutes to perform a heat treatment, thereby forming a liquid crystal alignment film. In addition, the above series of operations is performed with a UV irradiation dose of 100 to 10,000 J / m after post-baking. 2 By varying the exposure dose within the range of 100%, three or more liquid crystal cells with different UV exposure doses were manufactured, and various evaluations were performed in the same manner as in Example 1 using the liquid crystal cell with the exposure dose (optimum exposure dose) that showed the best alignment characteristics.
[0102] [Table 3]
[0103] [Table 4]
[0104] As shown in Table 4, Examples 1 to 23 had a better balance of various properties including inkjet coatability, AC image retention characteristics, VHR, reliability, DC image retention characteristics, and rubbing resistance than Comparative Examples 1 to 8. In particular, Examples 1 to 6, 8, 9, 11, and 14 to 22 were excellent, with all properties rated as "◎". In contrast, Comparative Examples 1 to 8 were rated as "×" for at least one of the properties of inkjet coatability, AC image retention characteristics, reliability, DC image retention characteristics, and rubbing resistance.
[0105] From the above results, it was revealed that the liquid crystal alignment agent containing the polymer [A] and the polymer [B] can reduce the residual image of the liquid crystal display element and produce a liquid crystal alignment film with high mechanical strength. In addition, it was revealed that the polymer [A] and the polymer [B] have good solubility, and it is possible to obtain a liquid crystal alignment agent with excellent coatability.
Claims
1. A polymer [A] having the following structural unit (U1) but not having the following structural unit (U2), A polymer [B] having the following structural unit (U2) and the following structural unit (U3), A liquid crystal aligning agent comprising: Structural unit (U1): a structural unit derived from a diamine having a partial structure represented by the following formula (1): Structural unit (U2): a structural unit derived from a diamine having a partial structure represented by the following formula (2): Structural unit (U3): a structural unit derived from a diamine having the following partial structure Y: Partial structure Y: -(CH 2 ) n - (wherein n is an integer of 1 to 20), -(CH 2 ) n+1 In the structure represented by -, any methylene group is -O-, -S-, -COO-, -NR 7 --, --NR 7 —CO—, —NR 7 -COO-, -NR 7 -CO-NR 8 -, or a structure in which the ring is replaced by a nitrogen-containing non-aromatic heterocyclic group (wherein R 7 and R 8 are each independently a hydrogen atom or a monovalent organic group. When n is 2 or more, -O-, -S-, -COO-, -NR 7 --, --NR 7 —CO—, —NR 7 -COO-, -NR 7 -CO-NR 8 - and nitrogen-containing non-aromatic heterocyclic groups are not adjacent to each other.), -O-, -S-, -COO-, -NR 7 —CO—, —NR 7 -COO- or -NR 7 -CO-NR 8 - 【Chemistry 1】 (In formula (1), X 1 and X 2 are each independently a divalent aromatic ring group. 1 The aromatic ring of 1 and a substituent is not bonded to a position other than the bonding position of the group bonded to "*", 2 The aromatic ring of 2 The substituent is not bonded to a position different from the bonding position of R and the bonding position of the group bonded to "*". 1 and R 2 are each independently a single bond, an alkanediyl group having 1 to 10 carbon atoms, or a substituted alkanediyl group having 1 to 10 carbon atoms, and at least one of R 1 and R 2 is an alkanediyl group having 1 to 10 carbon atoms or a substituted alkanediyl group having 1 to 10 carbon atoms. 1 and Y 2 are each independently * 1 -NR 3 -CO- or * 1 -CO-NR 3 - is. 3 is a hydrogen atom or a monovalent organic group. 1 " is Z 1 It represents a bond with . 1 is a single bond or a divalent organic group. m is 0 or 1. "*" represents a bond. 【Chemistry 2】 (In formula (2), A 1 and A 2 are each independently a divalent aromatic ring group. 1 is -NR 4 - or a divalent aromatic heterocyclic group. 1 When R is a divalent aromatic heterocyclic group, 5 and R 6 are each independently a hydrogen atom or a monovalent organic group. 1 -NR 4 -, then R 4 , R 5 and R 6 is either (i) or (ii) below. (i) R 4 R is a hydrogen atom or a monovalent organic group. 5 and R 6 are each independently a hydrogen atom or a monovalent organic group, or R 5 and R 6 and are combined together to form A 1 , -NR 4 - and A 2 It represents a ring structure formed together with (ii) R 4 and R 5 are each independently a hydrogen atom or a monovalent organic group, or R 4 and R 5 and are combined together to form A 1 and a nitrogen atom. 6 is a hydrogen atom or a monovalent organic group. "*" indicates a bond.)
2. The liquid crystal aligning agent according to claim 1 , wherein the polymer [A] and the polymer [B] are at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide.
3. The liquid crystal aligning agent according to claim 1 or 2, wherein the diamine having a partial structure represented by the formula (1) is a compound represented by the following formula (DA): 【Chemistry 3】 (In formula (DA), R 1 , R 2 , Y 1 , Y 2 and Z 1 is defined as the above formula (1).
4. The polymer [B] contains the structural unit (U2) in an amount of 5 to 95 mass% based on the total amount of diamine units contained in the polymer [B]. The liquid crystal aligning agent according to any one of claims 1 to 3.
5. A liquid crystal alignment film formed by using the liquid crystal aligning agent according to any one of claims 1 to 4.
6. A liquid crystal device comprising the liquid crystal alignment film according to claim 5 .
Citation Information
Patent Citations
Photosensitive diamine, liquid crystal alignment agent, and liquid crystal display element
JP2014205659A
Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display device, retardation film and method for manufacturing the same, polymer, and compound
JP2016006473A
Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display element, polymer, and compound
JP2016145954A
Liquid crystal aligning agent for forming liquid crystal alignment film for photoalignment, liquid crystal alignment film, and liquid crystal display element using the same
JP2016180973A
Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element
WO2016152928A1